2007
DOI: 10.4070/kcj.2007.37.3.103
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Carotid Intima-Media Thickness in Patients Who Underwent Percutaneous Coronary Intervention

Abstract: Background and Objectives:Increased carotid intima-media thickness (IMT) is known to be associated with adverse cardiovascular events in the patients with risk factors or established atherosclerosis. However, the prognostic importance of carotid IMT is uncertain in the patients who underwent percutaneous coronary intervention (PCI). We sought to evaluate the association of carotid IMT with major adverse cardiovascular events (MACE) and restenosis in the patients who underwent PCI. Subjects and Methods:The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Par défaut de méthode automatique qui offre plus de facilité et de précision [ 6 ], nous avons réalisé une mesure manuelle de l'EIM de la carotide commune. Malgré cette limite, ce travail a permis d’étudier les sujets à risque cardio-vasculaire dans la mesure où l'augmentation de l'EIM de la carotide est reconnue comme étant associée à un risque plus élevé de survenue d’événements cardio-vasculaires chez les patients présentant des FDR d'athérosclérose [ 7 ].…”
Section: Discussionunclassified
“…Par défaut de méthode automatique qui offre plus de facilité et de précision [ 6 ], nous avons réalisé une mesure manuelle de l'EIM de la carotide commune. Malgré cette limite, ce travail a permis d’étudier les sujets à risque cardio-vasculaire dans la mesure où l'augmentation de l'EIM de la carotide est reconnue comme étant associée à un risque plus élevé de survenue d’événements cardio-vasculaires chez les patients présentant des FDR d'athérosclérose [ 7 ].…”
Section: Discussionunclassified
“…This might be particularly valid because patients with CTDs also exhibit endothelial dysfunction 19 and medial wall thickening, both risk factors for failure of intravascular stents. 20,21 In the present study there was a nearly 50% increase in the proportion of CABG patient with CTDs over the past decade. Improved detection and coding of CTDs may further contribute to the rise of this diagnosis among patients undergoing CABG.…”
Section: Commentmentioning
confidence: 49%
“…However, on contrary to the findings of Kwon et al. [ 19 ], Lacroix et al. [ 37 ] performed univariate analysis and demonstrated that CIMT >0.7 mm was allied with an increased risk of cardiac events after coronary angioplasty compared with those with CIMT <0.7 mm ( p =0.03).…”
Section: Discussionmentioning
confidence: 76%
“…[ 24 ] and Kwon et al. [ 19 ], whereas on the other hand, Macdonald et al. [ 26 ] showed that age and sex had no association with restenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation